2020
DOI: 10.1111/jpn.13278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary energy level on growth performance, blood parameters and meat quality in fattening male Hu lambs

Abstract: This experiment was conducted to investigate the effects of different dietary energy levels on growth performance, slaughter traits, meat quality and blood biochemical parameters in fattening male Hu lambs. Sixty lambs were fed five iso‐protein diets which contained different levels of metabolizable energy in a completely randomized design for 70 days. At the end of study, fifteen lambs were harvested for further study. With the increase in dietary energy level, the daily weight gain and dry matter intake extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 53 publications
(85 reference statements)
6
34
2
1
Order By: Relevance
“…19 In general, live and carcass weights have the same variation tendencies. 20 In this study, in spite of obvious difference in live weight between the two breeds, there was no signi cant difference in carcass weight. If GLT is to achieve a carcass weight similar to that of STH, it needs to be much heavier.…”
Section: Discussioncontrasting
confidence: 45%
“…19 In general, live and carcass weights have the same variation tendencies. 20 In this study, in spite of obvious difference in live weight between the two breeds, there was no signi cant difference in carcass weight. If GLT is to achieve a carcass weight similar to that of STH, it needs to be much heavier.…”
Section: Discussioncontrasting
confidence: 45%
“…Yin et al [45] reported that the composition and content of amino acids are critical evaluation indices, which are associated with the flavor and nutritional value of meat. Our results showed that the meat of Tibetan sheep was rich in a variety of essential and nonessential amino acids like other livestock (e.g., Hu sheep, the Hengshan goat, and Yanbian cattle) distributed in the low-altitude areas of China [46][47][48]. It indicated that Tibetan sheep meat appears to be an excellent quality protein food source for native residents living at altitudes greater than 3000 m on the QTP.…”
Section: Meat Compositionmentioning
confidence: 68%
“…The tail fat plays a crucial role in maintaining the growth and above merits of sheep [15]. However, excessive tail fat deposition not only consumes more feed but also affects carcass weight and dressing percentage in sheep production [16,17]. So, it is of great significance to elucidate the mechanism of fat metabolism and deposition of fat-tailed sheep and the difference in tail fat size.…”
Section: Discussionmentioning
confidence: 99%